Case Report: De novo Vertebral Artery Dissection After Intravascular Stenting of the Contralateral Unruptured Vertebral Artery Aneurysm - You, Wei; Feng, Junqiang; Liu, Qinglin; Liu, Xinke; Lv, Jian; Jiang, Yuhua; Liu, Peng; Li, Youxiang (Frontiers in Neurology, 2021)
Spontaneous vertebral artery dissecting aneurysm has been increasingly attributed as a major cause of focal neurological deficits due to vertebrobasilar artery ischemia or subarachnoid hemorrhage (SAH). Although the development of spontaneous vertebral artery dissecting aneurysm (VADA) is rare, de novo VADA after treatment of contralateral vertebral artery (VA) is more less frequently observed. There are only a few reports related to de novo VADA after treatment of the contralateral VA in the medical literature. The mechanisms responsible for de novo dissection after treatment of unilateral VADA are still not clearly understood. In this manuscript, we report an unusual case of a patient with a de novo VADA after placement of a pipeline embolization device (PED) stent on the contralateral VA along with a thorough review of the literature. A 42-years old male patient was referred to the hospital with sudden onset of dizziness, nausea, and vomiting. Initial digital subtraction angiography (DSA) images demonstrated a VADA in the fourth segment of the left VA without the involvement of the posterior inferior cerebellar artery (PICA). There were no significant abnormalities found in the right vertebral artery. He underwent an endovascular pipeline embolization to treat the dissecting aneurysm (DA). Surprisingly, follow-up DSA imaging 14 months after the initial treatment showed a segmental dilatation and narrowing of the right VA, which suggested a de novo VADA on the right side that had occurred postoperatively. This was followed by a tent-assisted coil embolization therapy for occluding this de novo VADA. This patient showed an uneventful postoperative course with no neurological abnormalities. In addition to hemodynamic stress changes, the unique clinicopathological features of dissecting aneurysms may contribute significantly to the pathogenesis of de novo VA dissection. Given that VA in VADA patients may be vulnerable on both sides, it is important to consider the risk of de novo dissection after initial aneurysm treatment. The bilateral vertebral artery has to be carefully observed when treating any VADA patient to prevent any complications.